A taxonomic revision of the genus Pseudocamelina (Brasssicaceae, tribe Thlaspideae) - Esmailbegi, Shokouh; Lysak, Martin A.; Rahiminejad, Mohammad Reza; Mirtadzadini, Mansour; Mummenhoff, Klaus; Al-Shehbaz, Ihsan A. (Phytotaxa, 2017)
Pseudocamelina comprises nine species, of which seven are endemic to Iran and one each to Pakistan and Kurdistan Iraq. The new species P. bakhtiarica and P. kermanica are described, illustrated, and their relationships to nearest relatives are discussed. The new combination P. kurdica is proposed, and the genus Camelinopsis is reduced to synonymy of Pseudocamelina. Second-step lectotypifications are designated for P. camelinae and P. violacea.